(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
The objective of this research work, of a theoretical-descriptive nature, is to carry out a review of the literature on virtual education, management and the applications of the Resource Dependency Theory. The analysis was carried out based on previous works. Some considerations on the relationship of virtual education with the resource dependency theory (TDR) are also presented, in addition, a synthesis is included that shows the importance of its theoretical postulates in the organizational field. The findings of the work allow us to affirm that the management of virtual education requires the support of the environment, since they are not self-sufficient to generate all the resources and services they require, which leads them to participate in exchanges and transactions with other organizations. The research provides elements that facilitate the understanding of the application of the resource dependency theory in the field of virtual education management, which are relevant to the development of virtual education as it is to take advantage of the resources offered by the setting.